Epistomologi Kebenaran Terhadap Hukum - Pandri Zulfikar (Universitas Medan Area, 2022)
This article aims to find the truth of the law epistemologically, Epistomology has an exploration in the scope of how knowledge can basically be obtained and tested for truth, if it is specified in the realm of legal epistemology, the study is in an effort to listen to how legal knowledge can be obtained and how level of truth so that it can be a determinant of legal methodology. The meaning of truth according to the Big Indonesian Dictionary is the real situation. Truth is